Alejandría - Caride Bartrons, Horacio; Dal Castello, David; Molinos, Rita; Sabugo, Mario S.
Sobre la ciudad de Alejandría desde sus comienzos en la antiguedad hasta el presente.
Keywords: EGIPTO; ALEJANDRÍA; CIUDADES; HISTORIA